Is pro-Kremlin Disinformation Effective? Evidence from Ukraine. (January 2023) - Erlich, Aaron; Garner, Calvin
Can residents of Ukraine discern between pro-Kremlin disinformation and true statements? Moreover, which pro-Kremlin disinformation claims are more likely to be believed, and by which audiences? We present the results from two surveys carried out in 2019—one online and the other face-to-face—that address these questions in Ukraine, where the Russian government and its supporters have heavily targeted disinformation campaigns. We find that, on average, respondents can distinguish between true stories and disinformation. However, many Ukrainians remain uncertain about a variety of disinformation claims' truthfulness. We show that the topic of the disinformation claim matters. Disinformation about the economy is more likely to be believed than disinformation about politics, historical experience, or the military. Additionally, Ukrainians with partisan and ethnolinguistic ties to Russia are more likely to believe pro-Kremlin disinformation across topics. Our findings underscore the importance of evaluating multiple types of disinformation claims present in a country and examining these claims' target audiences.